A educação superior e os novos ambientes e redes digitais de formação de valores e expressão da confessionalidade - Monteiro, Robinson Grangeiro (2020)
This thesis deals with the formation of values and the expression of confessionality in new environments and digital networks in higher education. Structured in three axes, it proposes the creation of a Collaborative Virtual Chaplaincy (CVC). The research question originated from the need and importance of making Mackenzie’s virtual spaces of higher education an environment of value formation and expression of the university’s foundational and historical confessionality. The research assumed its theoretical frameworks in each of its three discursive axes – confessionality, value formation and collaborative networks – and worked from the status quo of both current distance learning and value formation initiatives, to indicate that a virtual collaboration network could complement the culture of presentiality and the formal exercise of Chaplaincy. The axis of confessionality sought to clarify the importance and historical evolution of confessionality for Mackenzie as a confessional institution, to the point of being an indelible mark of its institutional identity, advocated in its mission, vision and values. The conclusion is that it is unquestionable to disassociate Mackenzie from its history, deeply marked by its founding principles and their preservation, to the point of becoming institutional ethos. The axis of values proposed an analysis of the theme in two aspects. The first brought an innovative approach and a broader framework on the nature of these values, in terms of thinking moral formation of ethics, addressing these values as psychosocial and organizational constructs related to individual identity, group identity and organizational identity, establishing, from theoretical contributions brought from Social Psychology. The way in which values have constituted a social and organizational identity of Mackenzie was emphasized and, therefore, the use of collaborative networks as a group under social influence of this identity could contribute significantly to the proposal of forming values. A second aspect of this same axis dealt with morals, ethics and citizenship with perspectives of integration of Moral Psychology, Developmental Psychology, Philosophy and Education, with their respective most significant theoretical references, concluding that values are consolidated in social interaction by individual and his / her belonging groups, of which the family is the principal, but who have at school, at all levels, including higher education, the opportunity to be directed and mobilized for ethical and citizen actions, including assuming philosophical and religious foundations, such as Mackenzie's confessionality. Finally, the axis of collaborative networks was the challenge of how to align principles and concepts of the two previous axes, converging them towards a proposal to develop manifestations of mackenzist confessionality in existing and to be developed virtual contexts, consistent with the importance and necessity of fostering such structuring and transforming values of human relations in society, and always complementing what is already being done in traditional approaches linked to bodily presence for almost one hundred and fifty years at Mackenzie. The intentions were to discuss what collaborative networks are and how they can be used for the formation of values in educational contexts, based on the idea of networked learning and characterized as collaborative, meaningful and affective. The construction of these networks as ecosystems in 'places' in cyberspace has been discussed by the use of Information and Knowledge Technologies (ICTs) and also by Open Educational Resources (OER) for Networked Education, of hybrid nature (b-learning). , leading to the proposal of creating a Collaborative Virtual Chaplaincy (CVC), mentioned since the introduction as the contribution of academic and social relevance of the thesis, and characterized by all these technologies and pedagogical approaches mentioned. The thesis was concluded by designing initial principles for strategic planning and eventual action plan so that this CVC, if implemented, will complement the effective exercise of welcoming, value formation and the expression of confessionality, integrated with the culture of presence and exercise. Chaplaincy, assuming, already in Mackenzie's presential and virtual spaces, as an innovative initiative to serve society.